Timing-Driven NonuniformDepopulation-Based Clustering. (27th December 2009) - Liu, Hanyu; Akoglu, Ali
Abstract : Low-cost FPGAs have comparable number of Configurable Logic Blocks (CLBs) with respect to resource-rich FPGAs but have much less routing tracks. For CAD tools, this situation increases the difficulty of successfully mapping a circuit into the low-cost FPGAs. Instead of switching to resource-rich FPGAs, the designers could employ depopulation-based clustering techniques which underuse CLBs, hence improve routability by spreading the logic over the architecture. However, all depopulation-based clustering algorithms to this date increase critical path delay. In this paper, we present a timing-driven nonuniform depopulation-based clustering technique, T-NDPack, that targets critical path delay and channel width constraints simultaneously. T-NDPack adjusts the CLB capacity based on the criticality of the Basic Logic Element (BLE). Results show that T-NDPack reduces minimum channel width by 11.07% while increasing the number of CLBs by 13.28% compared to T-VPack. More importantly, T-NDPack decreases critical path delay by 2.89%.